The effect of pH on thrombin generation–An unrecognized potential source of variation - Søren Risom Kristensen; Jette Nybo; Shona Pedersen (Research and Practice in Thrombosis and Haemostasis, 2020)
Abstract Background When CO2 escapes from plasma, the pH of the plasma increases. In samples left open or kept in long‐term storage, the pH may increase considerably. Assays in which the ratio of plasma sample relative to the total volume including reagents is high may be sensitive to the pH of the plasma sample. Objective The aim was to investigate the effect of the pH of plasma samples used in the calibrated automated thrombin generation (CAT) assay in which the ratio (plasma sample) / (total volume) is high. Methods Plasma pH was increased by allowing CO2 to escape in open beakers before the CAT analysis. The effect of pH was also investigated by mixing plasma with buffers with different pH levels. Results At a pH close to 8.0, endogenous thrombin potential (ETP) and peak decreased considerably, whereas lagtime and time‐to‐peak were modestly increased. Mixtures of plasma and buffer with pH levels between 7 and 8 showed that ETP and peak decreased at alkaline pH; lagtime and time‐to‐peak were higher at acidic pH levels but were shortened, partly in contrast to first results, at alkaline pH levels. The addition of 4‐(2‐hydroxyethyl)‐1‐piperazineethanesulfonic acid buffer to plasma with a high pH attenuated the effects; however, the effect was most significant if added before the CO2 escaped. Conclusion Modifications of plasma pH can significantly alter thrombin generation. In alkaline samples, for example, after lengthy storage in a freezer where pH can increase considerably, thrombin generation is lowered. To minimize this effect, plasma should be stored in tubes filled to the maximum volume.